P03.11 Exploring tumor-intrinsic factors regulating the recruitment of myeloid-derived suppressor cells (MDSC) in pancreatic ductal adenocarcinoma. (1st October 2020) - Rambuscheck, C; Metzger, P; Hörth, C; Hennel, R; Bärthel, S; Falcomatà, C; Lauber, K; Endres, S; Saur, D; Schnurr, M; König, LM
Abstract : Background: Pancreatic Ductal Adenocarcinoma (PDAC) has very poor 5-year overall survival rate. Despite the encouraging effect of immunotherapy in other cancer types, clinical benefit in PDAC patients remains limited. One of the reasons for the lack of success is the immunosuppressive tumor microenvironment (TME), which is maintained by myeloid-derived suppressor cells (MDSC) and tumor-associated macrophages. High MDSC infiltration is associated with a poor survival in PDAC patients. Our project aims at identifying tumor-driven chemokines that influence recruitment of MDSC and establishment of the immunosuppressive tumor microenvironment. Materials and Methods: 45 PDAC cell lines generated from spontaneous tumors of genetically-modified mice harboring the characteristic driver mutations Kras G12D or PIK3CA H1047R were analyzed for their expression levels of CXCL1, CCL2, G-CSF and GM-CSF by qRT-PCR. In order to study the relationship between the chemokine/cytokine profile and the immune cell infiltration, selected tumor cell lines were implanted orthotopically in C57BL6 mice. Three weeks after inoculation blood, spleen and tumor were isolated and organ specific immune cell infiltration was analyzed by flow cytometry. To further characterize tumor-secreted factors tumor conditioned medium was generated and the concentration of 33 chemokines was analyzed in a multiplex assay. The chemokine levels were correlated with migratory capacity of splenic MDSC measured in an ex vivo chemotaxis assay. Results: CXCL1 significantly enhanced migration of polymorphonuclear MDSC (PMN-MDSC) in vitro, while migration of monocytic MDSC (M-MDSC) was predominantly skewed towards CCL2. Three weeks after tumor inoculation, MDSC populations in blood and spleen were expanded. Most intriguingly, PDAC cell lines with high CXCL1 or CCL2 levels in vitro showed significantly enriched intratumoral accumulation of PMN-MDSC and M-MDSC, respectively, suggesting that tumor-intrinsic chemokine secretion and not factors from the tumor stroma determined MDSC infiltration. The ex vivo chemotaxis assays revealed additional factors that modulate migration of MDSC into the TME. Conclusions: The in vitro gene expression levels of individual chemokines (CXCL1 and CCL2) determines the MDSC infiltration in vivo into the TME. Targeting the chemokine-receptor axis of MDSC subpopulations could be a promising approach in the treatment of pancreatic cancer. Funding: The project was supported by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) - Projektnummer 329628492 - SFB 1321 and the Förderprogramm für Forschung und Lehre (FöFoLe) funded by the Ludwig-Maximilians-Universität München. Disclosure Information: C. Rambuscheck: None. P. Metzger: None. C. Hörth: None. R. Hennel: None. S. Bärthel: None. C. Falcomatà: None. K. Lauber: None. S. Endres: None. D. Saur: None. M. Schnurr: None. L.M. König: None.